Islam di Indonesia atau Islam Indonesia (Studi Pergulatan Definisi dan Jatidiri ) - M. Amin Abdullah (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
This article seeks to discuss the problem of cultural acculturation, assimilation and adaptation in human life, particularly in its socio-cultural aspect of definition and identity. One of the issues denoted hybrid culture and its relation to the perspective of multiculturalism related to Islam and Indonesia. Queries include how to differentiate either the concept of Islam in Indonesia or Indonesian Islam, the construction of Indonesian Islam and lesson learned from the concept of Indonesian Islam. The study shows that the social and cultural modality served as the ultimate strength of Indonesian Islam. This includes religion and its connection with socio-cultural adaptation. The socio-cultural process bears some significant cultural aspects of literature, local songs, i.e., tembang, and architecture, i.e. joglo. Those cultural instances signified the adaptation agencies among Muslims in Indonesian context. In general, the notion between religion and its adaptation also occurred for some Muslims in the global context and experience.Key words: Identity, Indonesia, Islam, Cultural, Adaptation